EMPATHY IN HEALTHCARE: A COMPARATIVE STUDY OF CONSULTANT DOCTORS' PRACTICES IN PRIVATE AND PUBLIC MEDICAL SECTORS (Journal of Medical & Health Sciences Review, 2025)
Background: Empathy is a critical component of effective patient care, influencing clinical outcomes, patient satisfaction, and treatment adherence. Variations in empathy among physicians across healthcare sectors and specialties may impact the quality of care.Objectives:. To assess and compare empathy levels among consultant doctors working in public and private tertiary care hospitals in Peshawar, Pakistan, and to examine associations with demographic and professional characteristicsMethodology: A cross-sectional study conducted from May-August 2024 in public and private hospitals. Total of 115 consultants participated. Empathy was measured using the Jefferson Scale of Empathy (JSE). Demographic and professional data, including age, sex, specialty, and sector of practice, were collected via a structured questionnaire. Data were analyzed using IBM SPSS Statistics version 27. Independent-samples t-tests and one-way ANOVA were used, with statistical significance set at p